Márgenes precio-costo, competencia externa y participación del mercado en el sector manufacturero del Perú: 2002-2007 - Tello, Mario D. (2012)
Price-cost margins, external competition and participation of the market in the manufacturing sector in Peru: 2002-2007This paper analyzes the validity of four hypotheses on the relationship between the price-cost margin and import penetration as well as firms’ market concentration for a sample of Peruvian firms of the manufacturing sector in period 2002-2007. The first hypothesis states that an increase in the degree of import penetration reduces firms’ price-cost margins. The second hypothesis states that such a negative impact of the import penetration is greater the higher is firms’ concentration ratios. The third hypothesis propose the negative impact of import penetration is reduced the higher is firms’ concentration ratios. The fourth hypothesis states that the positive effect of a firm’ share of the market is decreasing. The evidence in the Peruvian case reject the first and third hypotheses and accept the other two.